Pain Care for Children with Cognitive Impairments: A Parent-Nurse Partnership - Choueiry, Juliana (Université d'Ottawa / University of Ottawa, 2023)
Parent-nurse partnerships are essential for pain care of children with cognitive impairments (CI), who experience a high prevalence and intensity of pain. However, researchers have not published findings about how parents and nurses partner for pain care of this population and the guiding partnership philosophy has been reported to be ambiguous. Thus, this qualitative interpretive descriptive study aimed to explore nurses’ experiences of establishing partnerships with parents for pain care of hospitalized children with CI. Videoconferencing interviews were conducted with eleven nurses. Verbatim transcripts were analyzed using an inductive, data- driven thematic analysis approach, resulting in eight main themes. Overall, nurses expressed uncertainty about providing pain care for this population and consequently, stressed the need to rely on parents. This study provides new knowledge relating to the realities of partnership practices. The findings have implications for nursing practice, education and research that may help to optimize pain care for children with CI.
Keywords: Pediatric Pain; Cognitive Impairment; Children with Disabilities; Nursing